2011
DOI: 10.1111/j.1523-5378.2011.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial on 14 versus 7 days of Esomeprazole, Moxifloxacin, and Amoxicillin for Second-line or Rescue Treatment of Helicobacter pylori Infection

Abstract: Second-line/rescue H. pylori eradication therapy with esomeprazole, moxifloxacin, and amoxicillin is very effective and well tolerated. Fourteen days of treatment significantly increase the eradication rate but also the rate of adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…As in other publications, antibiotic-based therapies were shown to have similar efficacy in our study [20,21,22,23,24,25,26]. We believe that using quinolon-based therapies in first-line treatment in areas where clarithromycin resistance is higher than 20% is an appropriate approach, since treatment options are limited and quinolon resistance is not a big problem yet.…”
Section: Discussionsupporting
confidence: 53%
“…As in other publications, antibiotic-based therapies were shown to have similar efficacy in our study [20,21,22,23,24,25,26]. We believe that using quinolon-based therapies in first-line treatment in areas where clarithromycin resistance is higher than 20% is an appropriate approach, since treatment options are limited and quinolon resistance is not a big problem yet.…”
Section: Discussionsupporting
confidence: 53%
“…None of these studies with 7–10 days of levofloxacin-containing triple therapies attained 90% or better treatment success. Two recently published studies reported that extending the length of quinolone-containing triple therapies to 14 days could achieve eradication success up to 95% (moxifloxacin) and 93.6% (levofloxacin) [35, 36]. Consequently, the current study achieved an eradication rate of 92.5% in the EAL-14 group in PP analysis but only 75.6% in the EAL-10 group.…”
Section: Discussionmentioning
confidence: 52%
“…Currently, ophthalmic release of the antibiotics between 7 and 14 days is suggested to increase bacterial eradication and to avoid possible adverse events [23]. The controlled release of moxifloxacin for 10 days, as achieved in this study, may lead to development of a moxifloxacin in situ gelling microparticles–bioadhesive delivery system that may be applied in one dose and will have a much higher efficacy than conventional eyedrop formulations have.…”
Section: Resultsmentioning
confidence: 92%